Western Colonization and the Powerlessness of the Islamic World - Cucu Jamilah; Ima Trimasary; Siti Lutfi Robi’atul Adawiyah; Imam Tabroni; Lie Jie; Cai Jixiong (Yayasan Adra Karima Hubbi, 2023)
Background. The Muslim world experienced several second peaks of glory during the reign of three great empires, the Ottoman, Safavid and Mughal (Indian) empires. Purpose. The purpose of this research is to reveal in depth the history of Islam during the 1800-1900 AD and broaden the horizons of knowledge for writers and readers. Therefore, it is necessary to reveal what factors caused the decline of Islam at that time as well as how the West dominated science at that time? Method. This research uses manuscript studies or known as research with the literature study method. The study of Islamic history texts in the modern period is also the object of this research which shows how this period displays the decline of Islam and the glory of the West. Results. The three great Islamic empires of the Ottomans, Safavids and Mughals, which were able to